Victimization, Fear of Crime, and Trust in Criminal Justice Institutions: A Cross-National Analysis. (June 2019) - Singer, Alexa J.; Chouhy, Cecilia; Lehmann, Peter S.; Walzak, Jessica N.; Gertz, Marc; Biglin, Sophia
Prior studies demonstrate that victimization and fear of crime independently affect criminal justice attitudes, but few have examined trust in criminal justice institutions. In addition, research has been primarily confined to the United States. Using data from the AmericasBarometer survey collected in the United States, Mexico, Argentina, and Brazil, the current study investigates the direct and indirect effects of criminal victimization and fear of crime on (a) perceived fairness of the courts, (b) trust in the police, and (c) overall trust in the criminal justice system. Results show that while the direct effects of victimization are mixed across countries and outcomes, fear of crime consistently mediates the effects of victimization on trust in criminal justice institutions.